Pembinaan Masyarakat dalam Budidaya Ternak Kambing Berbasis Teknologi Tepat Guna di Lembaga Mitra Peternakan, Kota Ternate: Community Development in Goat Cultivation Based on Appropriate Technology at Lembaga Mitra Peternakan, Ternate City - Hariyono, Dwi Nur Happy; Endrawati, Eny; Aji, Krishna (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Ternate City is the economic and trade center in North Maluku, where the agricultural sector ranked third as the main field of community employment after the service sector and processing industry. One of the community groups serving as a gathering place for breeders in Ternate is Lembaga Mitra Peternakan (LMP) located in Sasa and Jambula Villages. The problems faced by goat breeders in LMP include: the difficulty of getting superior males to mate with females, low livestock productivity due to inbreeding, the difficulty of getting continuous forage so that goats only fed tofu dregs waste, and the accumulation of manure around the pen which can cause odors and has an impact on livestock health. Based on the farmer's problem description, it was agreed that a community service activity would be held with the aim of providing guidance to livestock groups in goat cultivation through the application of appropriate technology at the LMP in Ternate city. The stages included surveys and outreach, community education, demonstrations and training, as well as monitoring and evaluation. All activities were attended by around 15 breeders. Farmers actively participated in VBC practices, silage feed processing and organic fertilizer. The silage and organic fertilizer produced can also be used by farmers. Farmers were able to manage the VBC concept, making silage and organic fertilizer independently. After the training activities, there was an increase in the knowledge and skills of breeders in practicing and applying appropriate technology in goat cultivation.